Insights Into the Role of Exposed Surface Charged Residues in the Alkali-Tolerance of GH11 Xylanase - Wu, Xiuyun; Zhang, Qun; Zhang, Lanzeng; Liu, Shijia; Chen, Guanjun; Zhang, Huaiqiang; Wang, Lushan (Frontiers in Microbiology, 2020)
Thermostable and alkaline- or acid-stable xylanases are more advantageous in agricultural and industrial fields. In this study, a rational structure-based design was conducted based on a thermostable GH11 xylanase TlXynA from Thermomyces lanuginosus to improved pH-tolerance. Four mutant enzymes (P1, P2, P3, and P4) and five variants (N1, N2, N3, N4, and N5) were constructed by substituting surface charged residue combinations using site-directed mutagenesis. Compared to the native enzyme, two mutants P1 and P2 showed higher acid tolerance, especially at pH 3.0, presented 50 and 40% of their maximum activity, respectively. In addition, four mutants N1, N2, N3 and N4 had higher tolerance than the native enzyme to alkaline environments (pH 7.0-9.0). At pH 9.0, the residual activities of N1, N2, N3 and N4 were 86, 78, 77 and 66%, respectively. In summary, an improved pH-tolerance design principle is being reported.